Няня для принцессы: роман / Ольга Хмельницкая - Хмельницкая Ольга (Няня - детектив, 2010)
Экземпляры: (201308) / Инвентарный номер: 48541 / Цена: 35.00 / Сис.шифр: Р2 48541 / Авт.знак: Х 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6